If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -1 = 2y + 11 Reorder the terms: -1 + 5y = 2y + 11 Reorder the terms: -1 + 5y = 11 + 2y Solving -1 + 5y = 11 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -1 + 5y + -2y = 11 + 2y + -2y Combine like terms: 5y + -2y = 3y -1 + 3y = 11 + 2y + -2y Combine like terms: 2y + -2y = 0 -1 + 3y = 11 + 0 -1 + 3y = 11 Add '1' to each side of the equation. -1 + 1 + 3y = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 3y = 11 + 1 3y = 11 + 1 Combine like terms: 11 + 1 = 12 3y = 12 Divide each side by '3'. y = 4 Simplifying y = 4
| 8x=12x-4 | | 207-6x=30x+15 | | x^2-3*x+14=0 | | 5(2-z)=2(2z-13) | | 11x+5=7x+21 | | 12y-6=3y+3 | | 8x-28=60 | | (X^2-1)(3x^2+3)=150 | | 9r+2=39r+7 | | 6-9x=151-44x | | 127-4x=3x+22 | | -54-8x=10x+18 | | 8x+4=68 | | 13+20x=20x+15 | | 2x+6=-34-8x | | 66-5x=9x+24 | | 4x+7=55-2x | | 1x+11=121+x | | 4x+37=11x-26 | | 6(5p-3q+1)= | | 6x-17y=20 | | 4x+40=7x+13 | | 2x-3.45=6.60 | | 1.5x-2.5=3.5x+13.7 | | 3c-2=5c-8 | | 75-3x=33x+19 | | 6t+5=2t+25 | | 6-9x=87-30x | | -40-4x=5-9x | | -175-10x=9x+15 | | m+6n-m+n-5+6n+3m= | | 91-2x=10x+19 |